2008
DOI: 10.1111/j.1541-4329.2007.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Food Safety Education to Middle School Students Using a Web‐Based, Interactive, Multimedia, Computer Program

Abstract: More than 76 million persons become ill from foodborne pathogens in the UnitedStates each year. To reduce these numbers, food safety education efforts need to be targeted at not only adults, but school children as well. The middle school grades are ideal for integrating food safety education into the curriculum while simultaneously contributing to national and state education standards in science, technology, and family and consumer sciences. For this project, a multimedia, self-paced online resource for deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…Broadly, these findings are consistent with the literature on middle school and college aged individuals, who also have low food literacy and poor food safety knowledge (Abbot et al, 2009;Green and Knechtges, 2015;Haapala and Probart, 2004;Lynch et al, 2008;Pedigo et al, 2009;Quick et al, 2013;Richards et al, 2008;Yarrow et al, 2009), limited food handling experience and skills (Abbot et al, 2012;Haapala and Probart, 2004;Morrone and Rathbun, 2003;Nesbitt et al, 2009), and who regularly engage in risky food handling practices and eating behaviours (Abbot et al, 2012;Altekruse et al, 1999;ByrdBredbenner et al, 2008;Haapala and Probart, 2004;Nesbitt et al, 2009;Patil et al, 2005). Although differences in study times and populations preclude specific comparisons, our findings from high school students may suggest that such factors may remain relatively unchanged across the middle school to college years.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Broadly, these findings are consistent with the literature on middle school and college aged individuals, who also have low food literacy and poor food safety knowledge (Abbot et al, 2009;Green and Knechtges, 2015;Haapala and Probart, 2004;Lynch et al, 2008;Pedigo et al, 2009;Quick et al, 2013;Richards et al, 2008;Yarrow et al, 2009), limited food handling experience and skills (Abbot et al, 2012;Haapala and Probart, 2004;Morrone and Rathbun, 2003;Nesbitt et al, 2009), and who regularly engage in risky food handling practices and eating behaviours (Abbot et al, 2012;Altekruse et al, 1999;ByrdBredbenner et al, 2008;Haapala and Probart, 2004;Nesbitt et al, 2009;Patil et al, 2005). Although differences in study times and populations preclude specific comparisons, our findings from high school students may suggest that such factors may remain relatively unchanged across the middle school to college years.…”
Section: Discussionsupporting
confidence: 80%
“…They often work in the food industry (Haapala and Probart, 2004;Usalcas, 2005;Yarrow et al, 2009) and are beginning to take greater responsibility for food handling (Burke and Dworkin, 2015). They also have low food safety knowledge (Abbot et al, 2009;Green and Knechtges, 2015;Haapala and Probart, 2004;Lynch et al, 2008;Majowicz et al, 2017;Pedigo et al, 2009;Q uick et al, 2013;Richards et al, 2008;Yarrow et al, 2009), lack safe food handling experience and skills (Abbot et al, 2012;Haapala and Probart, 2004;Majowicz et al, 2017;Morrone and Rathbun, 2003;Nesbitt et al, 2009), and engage in risky food handling practices (Abbot et al, 2012;Altekruse et al, 1999;Haapala and Probart, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the papers found, only two research papers contain empirical evidence related to learning styles: Lynch et al (2008) and Hwang et al (2012). Lynch et al (2008) developed Ootle-U to teach aspects of food safety.…”
Section: Adaptive Gbl Applications -Empirical Evidencementioning
confidence: 98%
“…This proved the existence of the correlation between spatial intelligence and the complementary educational images. Lynch et al (2008) investigated the influence of the web-based game on the learning styles and achievements on the sample of 300 US students. They concluded that the results of the experiment did not present statistically significant correlation between gameplay and learning styles.…”
Section: Discussionmentioning
confidence: 99%